Disseminated Cladophialophora bantiana disease in a patient with prediabetes. (14th November 2014) - Mansour, Anas; Jordan, Kim
Abstract : Cladophialophora bantiana, a dematiaceous fungus from the family Phaeohyphomycetes, is highly neurotropic and primarily reported as a rare cause of brain abscess. Pulmonary infection and disease outside the central nervous system is extremely rare, particularly in immunocompetent patients. We report an unusual case of disseminated cladosporiosis in a young man with a new diagnosis of prediabetes but no other identifiable risk factors for disease. Fungal cultures were positive for C. bantiana from brain abscess aspiration, vertebral bone cultures and subcarinal lymph node biopsy. Although the patient demonstrated initial good response to surgical debridement of brain abscesses plus antifungal therapy, he eventually expired from septic shock secondary to C. bantiana pneumonia and recurrent brain abscesses 2 years after initial diagnosis.